Anisotropic Terahertz Microscopy of Lysozyme in Different CrystalLattice Systems - McKinney, J. A.; George, D. K.; Deng, Y.; Markelz, A. G. (Biophysical Journal, 2021)
Long-range vibrational modes of proteins at terahertz (THz) frequencies havebeen associated with protein function and allosteric control. The characteriza-tion of these motions has been challenging due to energy overlap with waterabsorption and a large vibrational density of states. Recently it has been demon-strated both experimentally and theoretically that vibrational bands can be iso-lated using stationary sample anisotropic terahertz microscopy (SSTAM) fororiented samples, typically realized using protein crystals [1, 2]. In those earlymeasurements, inhibitor binding contrast was demonstrated for high symmetrytetragonal crystals. While high symmetry crystals are ideal for structural deter-minations, they can limit the types of vibrations observable in the ATM mea-surements. Here we show a survey of ATM measurements of triclinic,monoclinic and tetragonal crystals, demonstrating the unique signaturesobservable for the different symmetry groups, leading to a more completedetermination of the vibrational hot spots that may contribute to enzymatic ef-ficiency. The SSATM spectra indicate the presence of conserved vibrationalmodes near 40 cm-1 and 55 cm-1 for CEWL in triclinic, monoclinic and tetrag-onal lattice systems respectively. For CEWL in the monoclinic lattice system, aprominent band at 20cm1was consistently observed in the SSATM spectrabut not in the triclinic or tetragonal systems. The conserved bands may repre-sent vibrational modes that are unperturbed by crystal contact forces while thedifferences may be related to unique molecular orientation in different crystalsystems. 1.Niessen, K., Y. Deng, and A.G. Markelz,Near-field THz micropo-larimetry.Opt Express, 2019.27(20): p. 28036-28047. 2.Romo, T.D., A.Grossfield, and A.G. MarkelzPersistent Protein Motions in a RuggedEnergy Landscape Revealed by Normal Mode Ensemble Analysis. AcceptedJournal of Chemical Information and Modeling, 2020.